Migrações forçadas na américa latina: um diálogo a partir da teoria crítica de direitos humanos e a atuação da Corte IDH - Ceolin, Raquel Frescura (2021)
The hallmark of the hegemonic and Eurocentric conception of human rights is the universality and the foresight of these while guaranteed to everyone on an equal basis and without any discrimination. However, when observing reality, one observes the gap between what is said and what is done in human rights. This is because these rights are constantly violated to certain social groups, such as immigrants in the context of forced migration, who do not have access to the goods necessary for a dignified life. Hence the importance of reflecting on these rights from the perspective of critical theory, especially due to contributions made by Joaquín Herrera Flores in a dialogue with Latin American authors - the basic theory defined for the present research. For that, the delimited region was that of Latin America, contemplated by the Inter-American Human Rights System (ISHR), in order to understand the migratory flows that are placed in this context and the human rights scenario in a region marked by social inequality and a pendular movement between authoritarianisms and democracies - democracy being inseparable from human rights. With this, the question that guides the study is the following: what are the limits and perspectives existing in the ISHR, especially within the scope of the Inter-American Court of Human Rights, with regard to immigrants in the context of forced migration? The way used to answer this problem is supported by the dialectical method, considering that the object of the research will be approached from its contradictions, that is, from a critical review of human rights from the hegemonic conception to the lens of critical theory, from in order to unveil the migratory phenomenon, especially of forced migrations, in this perspective. As for the methods of procedure, there is the monographic and the historical. The research techniques are based on a bibliographic and documentary review, in order to establish the theoretical and conceptual outlines of the investigation and, finally, an empirical investigation of the contentious cases and advisory opinions of the Inter-American Court will be carried out, with a qualitative analysis of the selected documents. In this sense, the first section studies human rights from the hegemonic conception to the lens of critical theory, as well as the scenario of these rights in Latin America and the migratory phenomenon in the region, defining the pertinent concepts during the course of the research. The second section focuses on investigating contentious cases and advisory opinions of the Inter-American Court on the human rights of immigrants, enabling a critical reflection on these rights, especially from elements selected from the figure of the ethical diamond of Herrera Flores - in order to to understand human rights in their (real) complexity. It was concluded, in light of the assumptions raised, that despite the decisions of the Inter-American Court still lack compliance and effective repercussions within the scope of the nation-state, the IAHRS is a relevant and fundamental mechanism for the protection of human rights in the regional context, the from the emancipatory perspectives of the human rights of immigrants adopted by the Inter-American Court in an advisory and contentious manner.